Minimally invasive bunionette treatment: clinical and radiographic results - Lima, Alexander Felipe de Vete; Baumfeld, Tiago Soares; Maciel, Bruno Maciel; Baumfeld, Daniel Soares; Cordier, Guillaume; Nunes, Gustavo Araújo (Journal of the Foot & Ankle, 2020)
Objective: To report the clinical and radiographic results of surgical treatment of bunionette deformity with a minimally invasive technique without the use of hardware. Methods: This is a case series of 13 patients (14 feet) with a diagnosis of bunionette surgically treated with a minimally invasive osteotomy of the fifth metatarsal. All patients completed the American Orthopedic Foot and Ankle Society (AOFAS) score and a visual analog scale (VAS) for pain preoperatively and in the last follow-up visit. Radiographic measurements included the fourth-fifth intermetatarsal angle (4-5 IMA) and the fifth metatarsophalangeal (MTP-5) angle. Complications and level of patient satisfaction were also documented. Results: Mean follow-up was 12.3 months. The mean AOFAS score increased from 51.3 to 94.0, and the VAS score decrease from 7.5 to 1.1. The MTP-5 angle decreased from 11.5º to 2.3º, and the 4-5 IMA decreased from 9.8º to 3.6º. These outcomes showed a statistically significant difference (p<0.001). The only complication was hypertrophic callus formation observed in 3 feet (21.4%). There were no cases of infection, neurapraxia, wound dehiscence, nonunion, or deformity recurrence. Ten patients rated their outcome as excellent and 3 as good. Conclusion: Treatment of bunionette with percutaneous osteotomy of the fifth metatarsal without the use of hardware showed good clinical and radiographic results, with a low complication rate and a high level of patient satisfaction. Level of Evidence IV; Therapeutic Studies; Case Series.